Structure-function connectomics reveals aberrant left hemispheric developmental trajectory in autism spectrum disorder - Li, Zhifeng; Wang, Bin; Yang, Lan; Niu, Yan; Luo, Qin; Zhao, Shuo (Cerebral cortex (New York, N.Y. 1991), 2025)
Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by structural and functional brain differences relative to typically developing individuals. Although previous work has identified abnormalities in rich-club (RC) organization and left-right asymmetry in ASD, the developmental trajectory of these anomalies remains unclear. In this study, we examined how age influences structure-function coupling and structural proportions in RC networks using data from 140 participants (aged 5-26 years) drawn from ABIDE II. Our findings revealed significant, age-related differences in the left hemisphere of ASD participants compared to controls, with the RC network predominantly localized in this region. Furthermore, an interaction effect in local RC organization-though not in global RC or feeder connections-was observed between diagnostic groups and brain lateralization. Notably, rightward lateralization in local RC networks increased with age in ASD individuals, whereas it decreased with age in controls. These results underscore an atypical, age-dependent pattern of hemispheric asymmetry in ASD and offer new insights into abnormal neurodevelopmental trajectories within RC organization.